K-Nearest neighbor algorithm on implicit feedback to determine SOP - Muhammad Yusril Helmi Setyawan; Rolly Maulana Awangga; Nadia Ayu Lestari (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
The availability of a lot of existing Standard Operating Procedures (SOP) document information, users often need time to find SOPs that fit their preference. Therefore, this requires a recommendation system based on user content consumption by personalized usage logs to support the establishment of SOP documents managed according to user preferences. The k-nearest neighbor (KNN) algorithm is used to identify the most relevant SOP document for the user by utilizing implicit feedback based on extraction data by monitoring the document search behavior. From the research results obtained 5 classifications as parameters, with a final value of 3:2 ratio that shows the best distance value with the majority of labels according to the concept of calculation KNN algorithm that sees from the nearest neighbor in the dataset. This shows the precision of applying the KNN algorithm in determining SOP documents according to user preferences based on implicit feedback resulting in 80% presentation for SOPs corresponding to profiles and 20% for SOPs that do not fit the user profile. To establish SOP documents to show more accurate results, it should be used in a broad SOP management system and utilize implicit feedback with parameters not only in search logs and more on performance evaluation evaluations.